1994
DOI: 10.1677/joe.0.1430291
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of epidermal growth factor (EGF)/EGF receptor autocrine and paracrine mechanism in human trophoblast cells: functional differentiation in vitro

Abstract: We have studied the expression of epidermal growth factor (EGF) and EGF receptors (EGF-R) in isolated human trophoblast cells at various stages of differentiation and also the biological significance of the EGF/EGF-R autocrine and paracrine mechanism. Cytotrophoblast cells were isolated from human placental tissues of 6-9 weeks of gestation. Trophoblast cells underwent morphological and functional differentiation during in vitro culture. The expression of EGF and EGF-R protein and mRNA was studied in trophobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Morrish et al [7] documented increased release from primary human trophoblasts relative to Day 1, which is compatible with our studies. Amemiya et al [12] cultured primary trophoblasts to show high levels of CGB secreted on Day 1, which decreased and again peaked at Day 4-5, then decreased thereafter. These cultures released CGB over time much as explant cultures do ( [30]; this paper, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morrish et al [7] documented increased release from primary human trophoblasts relative to Day 1, which is compatible with our studies. Amemiya et al [12] cultured primary trophoblasts to show high levels of CGB secreted on Day 1, which decreased and again peaked at Day 4-5, then decreased thereafter. These cultures released CGB over time much as explant cultures do ( [30]; this paper, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of human chorionic gonadotropin (b-hCG, CGB) has also been used as a marker of villous trophoblast differentiation [1]. However, EGF has been shown to both increase [7,12,13] and decrease [14] CGB production in cultured trophoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…EGF is present in the decidua and amniotic fluid but the precise source and the regulation of its production during pregnancy remain somewhat controversial (Hoffman and Abramowicz, 1990;Bass et al, 1994). Trophoblasts can synthesize EGF (Hofmann et al, 1991;Amemiya et al, 1994) as well as TGFa, a growth factor with substantial sequence homology to EGF and that binds to the EGF receptor with the same affinity (Lysiak et al, 1993). Since trophoblasts express abundant EGF receptor (Tavare and Holmes, 1989), it is reasonable to hypothesize that an EGFPTGFcl autocrine/paracrine loop may be instrumental in regulating the sensitivity of these cells to cytokine-mediated killing.…”
Section: Esultsmentioning
confidence: 99%
“…These ligands have been shown to mediate various cellular functions, including proliferation, differentiation and migration (Basson et al, 1992(Basson et al, , 1994Amemiya et al, 1994;Chen et al, 1994;Traverse et al, 1994). In epithelial cells cultured as a flat monolayer on plastic, it has been shown that TGF-α and AR can act in an autocrine manner (Culouscou et al, 1992;Johnson et al, 1992;Li et al, 1992;Ziober et al, 1993;Qi et al, 1994).…”
mentioning
confidence: 99%